Assessing the impact of liquidity on the value of assets return - Khan, Muhammad Asim; Hussain, Arsalan; Ali, Muhammad Muzaffar; Tajummul, Mohsin Ali (UUM Press, 2022)
The concept of liquidity has been widely discussed in the literature of financial management to determine its influence on the different aspects of company’s financial performance. In a firm, there is a deficit and surplus in liquidity related to stock and it needs to be monitored to control the equity of a company. Deficit liquidity arises from a shortage in stocks and this can cause the profitability to below and this can cause a cashflow concern for the company. Hence, it is critical to evaluate the impact of liquidity on the returns and value of the study. Therefore, the following research is mainly conducted to investigate the effect of liquidity on the stock return from the context of two markets which are Pakistan and the United Kingdom. The data is gathered from total of 60 companies where the 30 companies belong to Pakistan whereas the remaining 30 companies are from UK. The time frame from which the data is collected is from 2005 till 2019 which makes a total time period of 15 years. With respect to the results of regression of the Pakistani data, it was determined that the illiquidity has significant and negative influence on the stock return whereas interest rate and HML has significant and positive influence on stock return. It is clear that the investors are highly concerned with the liquidity of the Pakistani companies as the increase of liquidity would cause reducing the stock return. While reflecting to the results of regression on UK data, it was identified that illiquidity has insignificant influence whereas the book to market, SMB, HML, IR and LNGDP has significant influence. Book to market and interest rate has negative influence on stock return whereas SMB, HML, interest rate and GDP have positive effect on stock return. Furthermore, recommendation and limitations are also highlighted in the study.